Integrating Project Based Learning (PBL) in Education 4.0 to Produce Higher Order Thingking Skills (HOTS) For Students in English Classes - Gita Almaida, Helsa; Nada, Chotrun; Novita Sari, Vinna (AMK : Abdi Masyarakat UIKA, 2022)
The key to successful learning lies in methods designed in learning that involve students learning knowledge and skills through project-based learning with structured processes, complex questions and authentic assignments carefully designed through the use of technology. Thus, the learning method is very appropriate with the integration of PBL in education 4.0. This study aims to produce HOTS students in learning English. Research data were collected using questionnaire, interview and observation instruments. The results showed that, (1) there was a significant effect of integrating PBL in education 4.0 on HOTS, (2) there was an effect of HOTS on English learning, and (3) integrating PBL in education 4.0 together influenced HOTS in English class.